Britain's future in Europe reform, renegotiation, repatriation or secession? - Emerson, Michael 1940- (Centre for European Policy Studies (CEPS) Rowman & Littlefield International, 2015)
If the Conservative Party wins the 2015 general election, Prime Minister David Cameron has promised the British people that a referendum on the country's future in the European Union will take place in 2017. A decision of this gravity needs to be made with the fullest understanding of its consequences, based on facts. This book offers a succinct, objective and comprehensive review of the evidence, the source of which is the British government's own research project, Review of the Balance of Competences between the United Kingdom and the European Union. This Review draws together over 3,000 pages of independent assessments of whether the distribution of powers between the EU and the member states is right or needs to be changed. The case for policy reform, renegotiation or repatriation of powers is presented across 32 different policy areas. The picture that emerges is far more nuanced and refined than the rhetoric that surrounds this crucial debate on Britain's future in Europe would suggest. The authors offer an analysis of the evidence and invite readers to draw their own conclusions from the information they present.